Some practical suggestions for dealing with the problems created by different interpretations of school histories (Historia, 2021)
Of  conferences there  is  no  end:  we  let  off   steam and  then  sinkback in  complacency, and in  the end nothing  is  done.   It  is  easier to  talkthan to  act.   The  passing of  resolutions is  only  the  initial  step.   A  greatdeal of  hard  work  lies  ahead of  us. ,As  I  see it  history should not be used to  promote better understandingbetween groups  or  nations;   history  should  not  be  used  to   serve  anypolitical  ends no  matter how lofty  our motives may be;  but  history shouldbe  taught in  such a  way that  misunderstandings do  not  arise and so  thatold  prejudices  are  not  reinforced  and  so  that  new  prejudices  are  notcreated
Keywords: History teaching; Interpretations in history; Teachers; School histories; History as subject